Improving Vocabulary Mastery of Sixth-Grade Students through the Index Card Match Strategy at SDN 8 Gedangan - Joko Wibowo Joko (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2026)
This study focused on addressing the issues of low vocabulary mastery, lack of motivation, and lack of involvement by utilizing the Index Card Match (ICM) strategy to improve vocabulary mastery, retention, motivation, and participation in group interactive learning. The caveat is that a Classroom Action Research (CAR) was conducted to find out if the Index Card Match (ICM) strategy was effective in improving vocabulary mastery with 16 sixth grader students at SDN 8 Gedangan with an administration of study from two cycles consisting of an initial and cycle tests, observation, questionnaire, rubrics, and passing successful identified by the scores rated ≥70 and participants demonstrated improvement with vocabulary retention, motivation, participation and engagement. The two-cycle Classroom Action Research (CAR) results found improved proficiency of sixth graders’ vocabulary mastery at SDN 8 Gedangan using the Index Card Match strategy from the initial and cycle tests, observation, and questionnaire reported, included an average score of 54.0 (6.25%) to 74.1 (100%). Active participation improved from (50%) to (90%), and positive feedback reported from (70%) to (96%) showed more motivation, engagement, and retention with vocabulary.